Characteristics of left ventricular hypertrophy in hypertensive patients - Díaz-Lazo, Aníbal (2020)
Objective: To determine the characteristics of left ventricular hypertrophy (LVH) in hypertensive people. Materials and methods: A descriptive, cross-sectional and prospective study conducted in the echocardiography laboratory of the Hospital Regional Docente Clínico Daniel Alcides Carrión in Huancayo, Peru. The sample consisted of 226 patients (calculated by formula) who met the inclusion criteria. A purposive non-probability sampling was used. LVH was diagnosed with an echocardiographic study. For the statistical analysis, chi square test, Student's t-test and odds ratio (95 % CI) were used. Results: The study population consisted of 226 (100 %) hypertensive patients. The average age was 67 years (range: 30 – 94). The most significant sociodemographic characteristics were being 60 years old and older (168 patients; 74.33 %) and female (140 patients; 61.95 %). Clinically, 96 subjects were overweight (42.47 %) and 45 were obese (19.9 %).  LVH was found in 73.89 % (167) of the patients. Severe, moderate and mild LVH were reported in 85 (37.61 %), 43 (19.03 %) and 39 (17.25 %) patients, respectively. According to the left ventricular geometric pattern, concentric hypertrophy was found in 57.52 % (130) and eccentric hypertrophy in 16.37 % (37) of the patients. Left ventricular diastolic dysfunction (LVDD) was found in 73.89 % (167) of the hypertensive patients. LVH was associated with a higher frequency of LVDD in 68.26 % (114) of the patients, while only 42.37 % (P < 0.001) of the patients without LVH had LVDD. Hypertensive patients with LVH have almost three times more risk of developing LVDD than those who do not have it (OR = 2.92; 95 % CI = 1.58 – 5.38). Conclusions: The hypertensive patients showed high rates of severe LVH, more than half presented a concentric ventricular geometric pattern, and they also had an increased risk of developing diastolic dysfunction.